The Influence of Perceived Organizational Support and Role Conflict on Employee Quiet Quitting: The Mediating Role of Job Satisfaction - Singh, Sukanksha; Bhatt, Alka Singh; Valliammal, M.; Bhalla, Ridhima; Sinha, Aparna; Bahadur, Shefali (International Review of Management and Marketing, 2025)
This study examines the influence of perceived organizational support and role conflict on employee quiet quitting, with job satisfaction serving as a mediating variable. Quiet quitting is characterized by employees disengaging from discretionary efforts and limiting their involvement strictly to contractual obligations and has emerged as a significant challenge in contemporary workplaces. This research investigates how the presence of supportive organizational environments and conflicting role demands shape employee attitudes and behaviours. A quantitative survey was conducted among 603 school teachers in Uttar Pradesh, India, and the data were analysed using structural equation modelling. The findings reveal that perceived organizational support negatively correlates with quiet quitting, while role conflict shows a positive association. Moreover, job satisfaction partially mediates both relationships, suggesting that employees who feel supported and experience lower role conflict are more likely to be satisfied with their jobs, thereby reducing the likelihood of quiet quitting. These insights underscore the critical importance of fostering supportive work environments and minimizing role ambiguity to enhance employee engagement and retention. The study offers practical implications for policymakers and administrators seeking to mitigate disengagement in educational institutions and similar work settings.